El teatro como recurso educativo para el desarrollo del lenguaje en los niños. - Gaona Torres, Renata Maolly (2022)
The present research is focused on theater as an educational resource for the development of language in students of the Elementary Basic Sublevel, whose problem is based on the fact that the country's education has been affected from early childhood onwards, in terms of language development, causing that sometimes the student can not communicate or express himself in an understandable way, becoming a problem when socializing with others, this leads to an analysis in terms of the teaching process in the first years of schooling in the area of Language and Literature. The general objective is to analyze theater as an educational resource for the development of language in the students of the Elementary Basic Sublevel of the Miguel Riofrío School of General Basic Education, and the specific objectives are: to identify the different types of theater as educational resources for the development of language and expression in children, to propose didactic strategies based on theater for the development of language and to design a proposal for educational improvement using theater as a resource for the development of language. The approach of this research work is of mixed character, because it allows giving objectivity to the object of study, with the obtaining of quantitative data that are explained with interpretations or meanings of the researchers, it will be possible to make the description of the study, as it is presented in reality, during the process different methods were applied, During the process, different methods were applied, as well as techniques such as the survey, used in the research work initially to know the feasibility and convenience of the work to be done and thus be able to identify the positive and negative factors of this research work whose importance highlights the development of language in children in the first years of schooling. Key words: drama, teaching resources, early childhood education, language development